Концептуальні основи гарантоздатних систем штучного інтелекту - Харченко, В.С. (Доповіді НАН України, 2025)
Запропоновано концепцію гарантоздатних систем штучного інтелекту (ШІ) на базі розвитку парадигми фон-Неймана (von Neumann paradigm, VNP), яку представлено теоретико-множинним описом з урахуванням різних складових — характеристик якості ШІ та систем ШІ (СШІ). Модель якості СШІ описується як упорядкована ієрархія характеристик довірчоздатності, поясненності, етичності, законності, відповідальності та їх підхарактеристик, що дозволяє визначити можливості застосування VNP для забезпечення виконання вимог до окремих характеристик. Розроблено модель відповідності перетворення вхідних та вихідних даних СШІ з врахуванням декомпозиції універсальної множини наборів даних (датасетів) на підмножини тих, що використовувалися для навчання та можливих некоректностей за певними характеристиками якості та різних типів відмов та кібератак на СШІ. Запропоновано використання принципу диверсності для впровадження VNP для забезпечення довірчоздатності та інших характеристик ШІ та створення гарантоздатних СШІ. The concept of dependent artificial intelligence (AI) systems based on the development of the von Neumann paradigm (VNP) is proposed. It is presented by a set-theoretic description that takes into account different qualitative characteristics of AI and AI systems (AIS). The stages and formulations of the evolution of VNPs from simple relay units to complex digital infrastructures and AIS are analyzed. One of the stages of VNP development is related to the fundamental work on the concepts and taxonomy of reliable and secure computing (A. Avizienis et. al., 2004). The AIS Quality Model (QM) is described as an ordered hierarchy of attributes (characteristics) of trustworthiness, explainability, ethicality, legality, responsibility and their specific sub-characteristics, which allows to determine the possibilities of applying VNP to ensure the required values of the characteristics. VNP is formulated for AIS in various representations such as “ trustworthy AIS form untrustworthy components”. AIS QM consists of the AI quality model and the QM of the system’s hardware-software platform. Application examples of AIS QM are analyzed. A model for matching and transforming input data into AIS output data is proposed, taking into account the decomposition of a universal data set into subsets used for training and possible anomalies in certain quality characteristics, as well as different types of failures and cyberattacks on AIS. It is proposed to use the principle of diversity in the implementation of VNP to ensure reliability and other characteristics of AI and to create dependent AIS. Models of reliable multiversion AIS are described and methods of reliability improvement are considered. These methods are based on various online testing schemes and application of versioning and structural redundancy.